Heavy metal intake and health risk implications from consumption of dried pulses in Trinidad and Tobago, W.I. Issue 3 (2nd July 2020) - Smith, Meagan; Mohammed, Faisal K.
ABSTRACT: The increase in urbanisation and industrialisation have contributed significantly to elevated concentrations of heavy metals in soils. The eventual uptake of heavy metals by agronomic crops could potentially affect human health based on consumption patterns in various regions of the globe. This study investigated the potential health risks to consumers of dried legumes in a small island developing state that rely primarily on the importation of those crops from major producers. Several varieties were analysed for selected heavy metals in which Cd and Pb were not detected and Cr was only present in certain legumes. The concentrations of Cu, Mn, Ni, and Zn were all below the established World Health Organisation (WHO) maximum permissible limit (MPL) and the target hazard quotient (THQ) and hazard index (HI) values were below one for all samples, suggesting no non-carcinogenic risk to consumers.